Engineering the Activity and Stability of MOF‐Nanocomposites for Efficient Water Oxidation. Issue 16 (3rd March 2021) - Wang, Yuan; Liu, Borui; Shen, Xiangjian; Arandiyan, Hamidreza; Zhao, Tingwen; Li, Yibing; Garbrecht, Magnus; Su, Zhen; Han, Li; Tricoli, Antonio; Zhao, Chuan
Abstract: Metal–organic frameworks (MOFs) are considered to be promising candidates for electrochemical water splitting. However, most MOFs are characterized by low electronic conductivity limiting their use as bulk materials for anodes and cathodes. Furthermore, the understanding of the critical parameters controlling the activity and stability of MOF electrocatalysts is still insufficient. Herein, a systematic analysis is presented of the key structural parameters controlling the oxygen evolution reaction (OER) performance and stability of a representative family of bimetallic NiFe‐MOFs, where the role of the metal cations on the accessible active sites and intrinsic activity can be investigated independently from the crystal structure. The models and in‐depth structural and morphological characterizations reveal a hierarchy of properties affecting the OER activity with accessible sites and intrinsic activity playing a major role in the charge transfer efficiency. Optimization of these properties and addition of a conductive support substrate leads to efficient MOF‐nanocomposite electrocatalysts achieving a low overpotential of 258 mV at a current density of 10 mA cm −2 with a small Tafel slope of 49 mV dec −1 and excellent stability for more than 32 h of continuous OER in alkaline medium. Abstract : A well‐dispersed bimetallic NiFe‐metal–organic framework (MOF) nanograin homogeneously grafted on graphene enhances electronic conductivity and provides a large amount of accessible active sites. In‐depth structural and morphological characterizations and models reveal a hierarchy of properties affecting the oxygen evolution reaction activity with accessible sites and intrinsic activity playing a major role in the charge transfer efficiency.